People financing entrepreneurs within and outside the family: Pandemic decline and resilience in cultures around the world - Ahmed Tolba; Ayman Ismail; Thomas Schøtt (Journal of Risk and Financial Management, 2021)
People may finance entrepreneurs, often family members. Here, the question is: how has the COVID-19 pandemic affected people's funding of family-related entrepreneurs and non-family-related entrepreneurs? The pandemic predictably reduced the funding of family-related entrepreneurs and especially the financing of non-family-related entrepreneurs. However, a culture supportive of family businesses may alleviate the declining funding of family-related entrepreneurs, predictably, while a secular-rational culture supportive of non-family businesses may alleviate the declining financing of non-family-related entrepreneurs. Similar to a field experiment, a globally representative survey was conducted before and after the disruption in 42 countries, interviewing 266,983 adults either before or after the disruption. The individual-level data are combined with national-level data on culture, amenable to hierarchical linear modeling. People's financing of family-related entrepreneurs and especially of non-family-related entrepreneurs are found to have declined with the COVID-19 pandemic. However, culture provides resilience, in that the declining funding of family-related entrepreneurs was alleviated where the culture supports family businesses, and the declining funding of non-family-related entrepreneurs was alleviated in societies with a secular-rational culture. The findings contribute to contextualizing business angel financing temporally, as embedded in time before and after the COVID-19 pandemic disruption, and societally, as embedded in culture providing resilience.
Keywords: 330; business angels; family-related entrepreneurs; non-family-related entrepreneurs; COVID-19; culture; family business culture; secular-rational culture; resilience